If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 2(x + -4) + -6 Reorder the terms: 12 = 2(-4 + x) + -6 12 = (-4 * 2 + x * 2) + -6 12 = (-8 + 2x) + -6 Reorder the terms: 12 = -8 + -6 + 2x Combine like terms: -8 + -6 = -14 12 = -14 + 2x Solving 12 = -14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -2x = -14 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -2x = -14 + 0 12 + -2x = -14 Add '-12' to each side of the equation. 12 + -12 + -2x = -14 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = -14 + -12 -2x = -14 + -12 Combine like terms: -14 + -12 = -26 -2x = -26 Divide each side by '-2'. x = 13 Simplifying x = 13
| 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z | | 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 | | 8p+5-3=9+7p | | 3(d-2)=15 | | 3s+5w=19 | | 5x-54+3x+16=180 | | 2x^2=x^2-6 | | -4y=-x+6+zy | | 16x^4+32x^3+24x^2+8x-80=0 | | tan(x)=-0.364+0.57735027 | | 6-3u=21 | | n-6=13-4 | | 5-3(2x-4)=5(4x+2)-32 | | 80+.10x=132 | | 4x+48=828 | | (x^2-200x+4000log(x)-7200)=0 | | X+12y=23 | | -3a-7a=-3a-6a+7 |